Natural Antioxidants and Vitamins Supplementation Shelters Adolescents from Upper Respiratory Tract Infection (International Journal of Child Health and Nutrition, 2020)
Context: Several decades of dietary research recommended the consumption of antioxidants and vitamins rich foods as a protective tool against a broad portfolio of diseasesAims: This study aims to test if oral supplementation of natural antioxidants and vitamins before the winter season, may reduce the occurrence of upper respiratory tract infection (URTI) in adolescents.Settings and Design: Natural antioxidants and vitamins supplements were given to 90 adolescents (45 males, and 45 females) from an orphanage against a placebo during three months in a double-blind fashion.Methods and Material: Saliva was collected before and after supplementation. The antioxidant activity of saliva was determined in vitro using electrolysis as a free radical generating system. Additionally, total antioxidant activity, glutathione and ascorbic acid levels in the saliva were evaluated before and after supplementation. The URTI frequency was recorded throughout the winter season (3 months).Statistical Analysis: All values were expressed as means ± SEM. Significance of the results was assessed using Student's t-test and Fisher’s testResults: Data indicated that only five individuals from the group that received antioxidants and vitamins supplements manifested URTI while 14 adolescents from the non-supplemented group showed symptoms of URTI. Biochemical analysis revealed that the saliva in provenance from the supplemented group exhibited a higher capacity to scavenge free radicals compared to its capacity before supplementation. This supplementation also increased the total antioxidant activity and the levels of both ascorbic acid and glutathione in the saliva.Conclusions: We concluded that oral intake of antioxidants and vitamins protects against URTI through increased antioxidant activity.